Effectiveness of Educational Videos for Learning The Concept of Bullying in Elementary School - Sofati, Siti; Ardy Wiyani, Novan (International Proceedings of Nusantara Raya, 2024)
Bullyingor bullying has become a serious problem in the primary school environment.These actionscan leavea deeppsychologicalimpacton children, especially in terms of adaptation and socialization.Bullyingis definedas aggressive behavior carried out intentionally and repeatedly, with an imbalance of power between the perpetrator and the victim.The impact of bullyingon victimsis very diverse, includinganxiety, depression, low self-confidence, to aggressive behavior.Giventhe magnitudeof this negative impact, a study was carried out to address the problem through the use of educational videos.The main purpose of this study was to help learners identify the dominant values conveyed in educational videos about bullying.Inaddition, the study also aimed to compare students ' understanding of bullying before and after watching the educational video.The datacollectionmethodusedin this study involvedinterviewsand observations, with the results presented in Tabular Form.Quantitativedataanalysisshowedan increasein students' abilityto identifymoralvaluescontainedin educational videos.Furthermore, significantdifferenceswere foundbetweenstudents' understandingbeforeand after being given educational video treatment. The results of the samplestudy showedthat afterwatchingthe educationalvideo, 36studentsunderstoodthe concept of bullyingwell, 3 students had less understanding, and only 1 student still did not understand bullying.The results obtainedcanbea valuablereferencefor various parties, including educators, parents, and policy makers.This researchis expectedto make an important contribution to efforts to create a safe and inclusive school environment.The results obtainedcanbea valuablereferencefor various parties, including educators, parents, and policy makers.